2019
DOI: 10.12659/msm.914781
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned from a Study of the Integration of a Point-of-Care Ultrasound Course into the Undergraduate Medical School Curriculum

Abstract: Background Point-of-care ultrasound (POCUS) diagnosis, performed by a physician at the patient bedside, is routinely used in emergency medicine and critical care. Although training in ultrasonography has become part of the medical school curriculum, POCUS can be challenging for medical students. This study aimed to assess the effectiveness of a one-day POCUS course in a group of final-year medical students by pre-course and post-course assessment of both diagnostic ability and changes in student c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 22 publications
3
10
0
1
Order By: Relevance
“…We have shown that a 2-day hands-on ultrasound course is a solid first step in an ultrasound curriculum for internal medicine. Participants perceive they have sufficient knowledge and skills to perform POCUS in real practice, which is in line with the effect of other ultrasound courses and ultrasound curricula [7][8][9][10]. It should be noted that the number of post-course responders is lower as compared to pre-course responders, which possesses a high risk of bias.…”
Section: Discussionsupporting
confidence: 64%
“…We have shown that a 2-day hands-on ultrasound course is a solid first step in an ultrasound curriculum for internal medicine. Participants perceive they have sufficient knowledge and skills to perform POCUS in real practice, which is in line with the effect of other ultrasound courses and ultrasound curricula [7][8][9][10]. It should be noted that the number of post-course responders is lower as compared to pre-course responders, which possesses a high risk of bias.…”
Section: Discussionsupporting
confidence: 64%
“…15 competence and self-confidence with time has also been demonstrated in medical students and academic physician faculty. 9,[16][17][18] The utility of recognizing the Dunning-Kruger Effect is helping junior physicians navigate their professional development, clinical expertise, and sense of self-confidence. It encourages physicians to be introspective, recognize their weaknesses, and beware of the limitations of self-confidence as a measure of clinical competency.…”
Section: Applicability To Residency Trainingmentioning
confidence: 99%
“…Published programs have demonstrated the feasibility of integrating a POCUS curriculum into UGME and emerging data suggests that students perceive value in this effort. Focused ultrasonography can be used as a useful aid in teaching anatomy to medical students, learning physical exam skills; and has been received quite positively by medical students at several institutions [8,21]. A national survey of 82 medical schools, where 51 report some ultrasound integration into UGME, found that > 90% of students preferred ultrasound incorporated into their program, > 80% Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Only a handful of schools reported the impact of ultrasound education UGME in measurable formats like enhanced performance on standardized tests, enhanced physical exam skills by providing real time visual feedback on examination finding, improving the diagnostic accuracy of pathological exam findings, enhancing critical thinking skills by providing real time information corroborating or refuting differential diagnosis [5,[18][19][20][21]. One school conducted a retrospective analysis of the Comprehensive Osteopathic Medical Licensing Examination of the United States (COMLEX-USA) level 1 scores in anatomy, diagnostic technology, and osteopathic principals and practice.…”
Section: Evaluation Of Programmentioning
confidence: 99%